Atlas of northeastern yiddish: importance of maps in linguistic research - Beconytė, Giedrė; Katz, Dovid (Geodesy and Cartography, 2011)
The paper introduces the application of cartographic methods to research on a culture at the last moment of its in situ existence. The atlas in progress seeks to determine the historic external borders, the internal differentiation and the cultural and linguistic structure and characteristics of Líte ([lítə] – the territory of traditional jewish Lithuania (coterritorial with today’s Lithuania, Latvia, Belarus, and swaths of northeastern Poland, northern and eastern Ukraine and westernmost Russia). The main linguistic data were initially organized by lists of locations where use of a particular form had been documented. Sparse information has been converted to a relational database model, linked to geographic data (locations) and analyzed. The discovered information was sufficient to approximately locate spatial clusters that were not thought to be recoverable when the project was initiated. The results of the geographic analysis are presented in the form of maps in the evolving draft of Litvish: An Atlas of Northeastern Yiddish that is accessible for preview at http://www.dovidkatz.net/WebAtlas/AtlasSamples.htm. The structure of the linguistic database also enables publication of the data as a web service representing the location of occurrences of linguistic forms on a larger scale map. However, the small scale linguistic maps represent characteristics of the dialect areas that are more convenient for readers who specialize in the relevant language and culture, but are not familiar with geospatial technologies. Šiaurės rytų teritorijos jidiš atlasas: žemėlapių svarba atliekant lingvistinius tyrimus Santrauka. Aptariamas ir iliustruojamas kartografinių ir erdvinės analizės metodų taikymas atliekant lingvistinius tyrimus. Lietuvos jidiš tarmių žemėlapiais siekiama atskleisti iš esmės jau išnykusios kultūros teritorinę įvairovę, istorines ribas, kultūrinius ir lingvistinius ypatumus. Tyrimų objektas yra tradicinė Lietuvos žydų teritorija Líte, apimanti didžiąją dalį dabartinės Lietuvos, Latvijos, Baltarusijos bei šiaurės rytų Lenkijos, šiaurės ir rytų Ukrainos, vakarinės Rusijos pakraščio teritorijas. Kuriamas atlasas apima per 30 žemėlapių, kuriuose pavaizduota dažniau pasitaikančių žodžių formų įvairovė ir teritorinė jų sklaida. žemėlapiai sudaryti naudojantis GIS duomenų baze, kurioje registruoti D. Kadz beveik 20 metų trukusių tyrimų Lietuvos žydų teritorijoje duomenys. Prielaidos apie Lietuvos jidiš dialektų paplitimą buvo tikrinamos erdvinės statistikos metodais. Nors duomenys nėra labai išsamūs ar vientisi, sudarytuose žemėlapiuose aiškiai matyti skirtingų lingvistinių formų paplitimo teritorijos, šių teritorijų homogeniškumas ar heterogeniškumas, jų kitimo laikui bėgant ypatumai. žemėlapiai sudaryti taip, kad būtų lengva pastebėti ir interpretuoti juose įžvelgiamus dėsningumus. Atlasą galima rasti internete: http://www.dovidkatz.net/WebAtlas/AtlasSamples.htm Reikšminia žodižiai: Kartografija, lingvistiniai tyrimai, lingvistiniai žemėlapiai, dialektai, jidiš, Lietuvos jidiš. Атлас северо-восточного идиш: роль карты в лингвистических исследованиях Резюме. В статье обсуждается применение картографических методов в лингвистических исследованиях территории северо-восточного (Литовского) идиш. На составленных авторами картах представлено распределение характерных форм идиш на территории современных Литвы, Латвии, Беларуси и соседних стран. Данные, собранные во время экспедиций по территории Литовского идиш, неоднородны и недостаточны для статистических исследований, тем не менее карты позволяют выявить интересные пространственные закономерности и глубже познать культуру на грани исчезновения. Карты составляют атлас, с которым можно познакомиться на сайте: http://www.dovidkatz.net/WebAtlas/AtlasSamples.htm Ключевые слова: картография, лингвистические исследования, лингвистические карты, диалекты, идиш, Литовский идиш.